Power System Analysis of Steam Power Plant Using ETAP at ULPL Indralaya South Sumatra - Umi Rasyda, Thriska Dewi; Afandi, Arif Nur; Rahmawati, Yuni (Jurnal Teknologi Informasi dan Pendidikan, 2023)
PT PLN (Persero) UPDK Keramasan have three group work units in South Sumatra Province which is study has located in Ogan Ilir Regency namely PT. PLN ULPL Indralaya. This study is one steam turbine generator unit often experiences shutdown due to several factors. One of them is out of service for the protection operating system on the 4 MVA to 11.5/6.9 kV transformer unit when there is a disturbance so that there is an inter-trip to the upstream system which results in a blackout system. We analyzed the disturbance using ETAP software. We made three analyzes there are load flow, short circuit and relay coordination. As study results submitted to PT PLN ULPL Indralaya is to scenario 3 for the analysis of the resulting lower flow is a decrease in load of about 63% for short circuit value obtained between 0.011 to 50.776 kA also relay coordination should be adding devices such as IDMT curve Long Time Inverse.